Immunity and vaccine development efforts against Trypanosoma cruzi - Rios, Lizette E. (2019)
Trypanosoma cruzi (T. cruzi) is the causative agent for Chagas disease (CD). There is a critical lack of methods for prevention of infection or treatment of acute infection and chronic disease. Studies in experimental models have suggested that the protective immunity against T. cruzi infection requires the elicitation of Th1 cytokines, lytic antibodies and the concerted activities of macrophages, T helper cells, and cytotoxic T lymphocytes (CTLs). In this review, we summarize the research efforts in vaccine development to date and the challenges faced in achieving an efficient prophylactic or therapeutic vaccine against human CD.